Bioassay guided isolation of bioactive components from the stem bark of entada spiralis ridl. (Sintok) - Aiza binti Harun (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2014)
Entada spiralis Ridl. which is locally known as 'sintok' or 'beluru' is a perennial plant species belonging to the family of Leguminoceae. Traditionally, the stem bark had been used as shampoo when rubbed in water to treat scalp and body care, while the decoction of its root had been used to treat syphilis and bloody defecation. The bioactivity studies against dermatophytes and bacteria and phytochemical studies of the stem bark of this species are the first time reported in this thesis. The froth test of the stem bark of E. spiralis indicated the presence of saponin, and the Liebermann-Burchand test had confirmed the existence of triterpenoid saponin. The extract of the stem bark of E. spiralis was prepared by extracting with petroleum ether, chloroform and methanol sequentially. Methanol extract (polar extract) gave the highest percent yield. The bioactivity assay results revealed that Microsporum gypseum was the most susceptible dermatophyte towards all extracts with minimum inhibitory concentration MIC values of methanol extract at 0.78 mgl/mL. Staphylococcus epidermidis was found to be the most susceptible bacteria towards all extracts with MIC values of methanol extract at 0.195 mg/mL, 3.125 mg/mL for chloroform extract and for petroleum ether extract at 0.78 mg/mL. Methanol extract was further fractionated using vacuum liquid chromatography (VLC) since it displayed promising antimicrobial activity against dermatophytes and bacteria. Among all fractions that were assayed for bioactivity, fraction FA1 was found to be the most effective fraction with MIC at 0.097 mg/mL and 0.195 mg/mL against Trichophyton mentagrophytes and M. gypseum respectively. Other fractions showed higher MIC value at 3.125 mg/mL for fraction FA2, FA3 and FA5. The fraction FA4 gave MIC value at 6.25 mg/mL. Fraction FA1 had also been screened to contain a greater number of active compounds compared to other fractions with respect to the number of clear zone of inhibition through the agar overlay bioautography assay. The active compounds from fraction FA1 were known as terpenoid compounds as detected by spraying the reference chromatogram with vanillin/sulfuric acid reagent. Therefore, fraction FA1 was chosen for isolation using separation methods of circular chromatography on silica gel (chromatotron) and solid phase extraction (SPE). About ten, compounds were successfully isolated and were indentified based on spectroscopic analysis of UV, HPLC, MS, FTIR, 1-D NMR (1H, 13C and DEPT 135) and 2-D NMR (H-H COSY, HMQC, HMBC) at 600 MHz. AC1 compound was identified as penta-2-acetoxy-β-D-digitoxopyranosyl-(1→2)-fructofuranosyl-(6→4)-β-D-glucopyranosyl-(1→4)-glucopyranosyl-(1→2)-β-D fructofuranosyl-(6→1)-β-D-glucopyranosyl-(4→1)-acetylglucosamine. AC2 was elucidated as β,D-glucopyranosyl(1→2)-β,D-glucopyranosyl)-(1→3)-β,D-xylopyranosy-l(1→4)-α,L-rhamnopyranosyl)-(1→3)-β,D-glucopyranos yl(1→3)-β,D-glucopyranoside. AC3 was known as 16-β-D-arabinofuranosyl-15-β-D-xylopyranosyl-5,8,9,10-tetrahydroxyl-17,18,19,20-tetramethyl diterpene ester. AC5 was identified as 28-α,L-rhamnopyranosyl-18,21,22-trihydroxy-12-en-29-(2-acetylamino-β-D-glucopyranosyl) triterpene ester. AC9 was elucidated as 4-(β-D-glucopyranosyl)-1-hydroxybenzene-(20-hydroxyl-18,19-dimethylcyclotetradecanol) benzoate. AC4 and AC7 were classified as triterpenoid ester. AC8 and AC10 were determined as diterpenoid ester.